Economic policy uncertainty on stock market risk contagion: a network-based approach - Shao, Hualu; Wang, Di; Zhou, Baicheng (Frontiers in Physics, 2024)
This study selects data from the Economic Policy Uncertainty (EPU) and the stock index volatility of the top seven global economies in 2021 to study the impact of EPU on risk contagion in global stock markets using the full-sampled time from January 5, 1998, to April 22, 2022. And three different types of global crises are selected for subsample studies (the 2008 financial crisis, 2019 Brexit, and 2020 COVID-19 as examples) to construct a global EPU and stock market risk spillover network and to study the impact of EPU on the transmission direction and intensity of stock market risk in each country under each period. The findings are as follows. First, economic policy uncertainty has both direct and indirect effects on risk contagion in stock markets across countries. The full-sampled period mainly plays an intermediary role, mostly by transmitting minor risks to a country first and then expanding in the trading among countries. However, it has a significant direct effect on countries with large economy size in the period of Brexit and COVID-19. Second, the intensity and structure of global stock market risk spillovers are time-varying. Stock markets in developed economies such as the United States and Europe play a major role, but no country remains the issuer and recipient of risk spillovers. Third, crises of different stages and types can bring huge shocks to global EPU and stock markets. The speed and effects of shocks from public health security crises are much greater than those from financial and political risk crises. In light of the above findings, investors and policymakers in different countries are expected to strengthen cooperation in financial risk prevention, enhance risk early warning, and pay special attention to shocks brought by public health events to prevent the recurrence of large cross-border financial risks.